A comparison of the battery fault tolerance ability of modular multilevel converters with half-bridge and full-bridge submodules - Liang, Gaowen (2021)
The modular multilevel converter (MMC) is a promising option to integrate battery energy storage systems (BESSs) into the power system. Both half-bridge submodules (SMs) and full-bridge SMs can be used to implement an MMC. For MMC-based BESS, it is important to have sufficient battery fault tolerance, which means the system can operate normally even when some SMs have faulty batteries or no batteries. This paper analyzes and compares the battery fault tolerance of MMC-based BESSs with half-bridge and full-bridge SMs. According to the quantitative comparison, the MMC with full-bridge SMs has considerably higher tolerance to battery faults when the active power requirement is relatively high. Simulation and experimental results are provided for the verification of the proposed analysis.